Organized Chronic Subdural Hematoma Mimicking Acute Epidural Hematoma - Jun Cao; Zhichun Wang; Cegang Liu; Jun Shen; Jincheng Fang (Case Reports in Medicine)
Background. Chronic subdural hematoma is a common disease in neurosurgery, but organized chronic subdural hematoma is rarely seen clinically. This article reports a case of misdiagnosis of organized chronic subdural hematoma as acute epidural hematoma. Through literature review, the causes of misdiagnosis and the treatment methods of organized chronic subdural hematoma are discussed. Case Description. A 70-year-old male patient was admitted to the hospital due to headache and dizziness after head trauma. Emergency head CT reported “left frontotemporal parietal epidural hematoma.” Because the head CT showed that the hematoma occupying effect was obvious, an emergency “intracranial hematoma evacuation” was performed. After opening the skull during the operation, no epidural hematoma was seen. Upon incision of the dura mater, the outer membrane of organized chronic subdural hematoma was found. When the outer membrane was cut open, a large amount of reddish-brown silt-like materials was found in the capsule cavity. The inner membrane was not forcibly removed. Postoperative head CT showed that the organized chronic subdural hematoma was basically cleared. Conclusion. The early symptoms of organized chronic subdural hematoma are atypical, with insidious onset and easy misdiagnosis. By carefully inquiring about the medical history and carefully reading the head CT, such misdiagnosis can be avoided. Craniotomy is currently an important treatment option for organized chronic subdural hematoma.